Western civilization - Perry, Marvin (Houghton Mifflin Company, 2007)
Western civilization eighth Edition, maintains a firm grounding in political history, while covering intellectual history (particularly the significance of ideas and contributions) to greater and deeper extent than any other text for the course. Known for its accessible writing style, this text appeals to students and instructors alike for its brevity, clarity, and careful selection of content including its enhanced focus on religion and philosophy. Updated with more recent scholarship, the Tenth edition retains many popular features, including comparative timelines, full-color art essays, profiles, and primary source boxes in each chapter. New technology resources (available separately), including CourseMate with interactive eBook, make learning more engaging and bring history concepts to life